A regulamentação jurídica da inteligência artificial no Brasil, como garantia do não retrocesso do direito ao trabalho - Dallacort, Luis Ângelo (2021)
Artificial Intelligence will promote, in the coming years, intense transformations in social paradigms, imposing the need for serious discussions about the possible impacts arising from its use. Among the many areas in which Artificial Intelligence will be felt, the job market, unquestionably, will be one of the most strongly impacted. Although there are doubts about the professions of the future, about which human jobs will be replaced by this technology and how many professions will succumb, one certainty exists: it is necessary to adopt measures in the present, which enable an adequate market transition. Therefore, the regulation of Artificial Intelligence is imperative to ensure that, in both the public and private sectors, this transition occurs, based on the creation of new opportunities for workers, preserving their right to work. The problem of this study is based on the investigation of how the regulation of Artificial Intelligence in Brazil can guarantee the non-retrogression of the social right to decent work. To achieve this, three specific objectives were established, namely: investigating how Artificial Intelligence applies and impacts society and the economy; analyze the effects of Artificial Intelligence on labor law; reflect on how the regulation of Artificial Intelligence enables its development in Brazil, while promoting and preserving decent work. Using the operational logic of the hypothetical-deductive method, a bibliographic and documentary search was carried out in books, periodicals and legislation. It was possible to conclude that the regulation of Artificial Intelligence would enable the existence of well-defined guidelines for strategic actions that could lead to social transformation. In fact, in countries with well-defined bases and strong legislation, legal certainty is also guaranteed, an essential element for attracting investments. Likewise, the professional training of citizens must be provided for the new demands of a job market impacted by Artificial Intelligence. All of these actions can lead to a positive result, of both individual and social development, resulting in the progress of the nation that is prepared for the challenges of the new technological era in force.